Pencitraan 3D Data Geolistrik Resistivitas dengan Rockworks Berdasarkan Hasil Inversi Res2DInv untuk Mengetahui Persebaran Batuan Konglomerat di Desa Surodadi, Kecamatan Gringsing, Kabupaten Batang - Taufik Nur Fitrianto; Supriyadi Supriyadi; Teguh Maulana Mukromin (Department of Physics, Sebelas Maret University, 2017)
Research was conducted to determine distribution of Conglomerate in Surodadi Village, Gringsing, Batang. The data acquisition used Schlumberger array. The length of line is 165 m and 15 m electrode spacing. The data processing used Microsoft Excel and 2D imaging used Res2Dinv. Then 3D imaging used Rockworks from result of Res2DInv inversion. The position data was used on UTM coordinate from position data each of electrode. The data acquisition was done at two parallel lines. In this area was found two types of rocks; tuffaceous sandstone and conglomerate. The conglomerate with resistivity values higher than 180 Wm is distribution on southeast research area at the depth 5 m – 25 m. While the tuffaceous sandstone layers is distribution on northwest research area.